Strategisk och taktisk planering samt länken där emellan : analys av planeringsprocessens genomförande vid SCA Skog - Eriksson, Malin (SLU/Dept. of Forest Resource Management, 2008)
To effectively manage a forest resource for both economic and other values good planning is required. The problem is complex since you want to know which forest to cut and when. Often a hierarchical planning structure is applied, including strategic (long-term), tactical, (medium-term) and operational level.